Assess The Degree Of Malnutrition And Associate The Sociodemographic Factors Among Under Five Children In Selected Rural Community - Dhanalakshmi, M. Angelin; V. Valarmathi, V. Valarmathi; J C, Helen Shaji; Joysmerlin. J, Joysmerlin. J; Benisha. B, Benisha. B; Sundar.V, Sundar.V; Karthik. L, Karthik. L (Journal of Neonatal Surgery, 2025)
Nutrition plays an important role in the physical, mental and emotional development of a child. Infants and pre-school children are the most vulnerable group. Children are the first priority in human resource development for several reasons: Young children are the most vulnerable, requiring special care and protection. The early years lay the groundwork for cognitive, social, emotional, physical, and motor development. Investing in early childhood development is crucial for the economic growth and development of any nation. Early childhood is a critical period when the foundation for life-long learning and development is laid. In essence, investing in young children is a crucial investment in the future of a nation. The main aim of the study is to assess the nutritional status among under five children. And associate the nutritional status among under five children and their demographic variables. A quantitative approach was used. This study sample consists of 100 under five children who fulfilled the inclusive criteria were selected by purposive sampling technique. A structured questionnaire and physical assessment method were used for data collection. The experts in the field of nursing and biostatistician were done content validity of tools. The data were analyzed in the form of descriptive and inferential statistics. The findings revealed that 32% children in the first degree of malnutrition , 29% children in the second degree malnutrition and 4% children in the third degree malnutrition. 35% are normal. This study remained that periodical nutritional education and regular monitoring of nutritional status of the under five child